Reforma administrativa e gestão de políticas sociais em Mossoró: a falácia dos atores institucionais e sociais - Menezes, Suzaneide Ferreira da S. (2009)
The thesis entitled The administrative reform and social political management in Mossoró: the institutional and social staff's falacy. Comprehends a moment of apprehensiveness and analysis in the reestrcturing process of the city, whose process will show the formation of strategies and deployment of its relation with the social political affectiveness. It represents a single moment in the approach of such a kind of experience in the city. The analysis starts from the third mandate of the Mayor Rosalba Ciarlini Rosado, during the quadriennium 2001/2004, for being the time in which the public management got materialized, such as in the operational way of the social politics. For that, we delimitate this study in two distinct moments: the first one refers to the reform elaboration from the creation of the additional law nº 001/2000 GP/PMM: the second one refers to a practical reform from the social and institutional staff's speech. Within that scenary it was seen that the approaching, though partially, the State Reform and, consequently, the master plan of the state apparatus, which were made of theoretical matrices of such a project locally. However, that is a complex experience, that required the use of field and documental research for the proposed investigation and at the same time, prove the guiding hypothesis of it, what means a grouping of areas like: education, healthy, and social development in only one department City Citizenship Department that is able to materialize a new intitutional arrangement, according to the management principles in the public administration at the govern local level, configuring a reform and not just an institutional adequacy. In that context, it got necessary to apprehending the institutional and social actors' falacy as a way to prove or not the presented hypothesis. Among the first staff, we have the mayor's direct leaders and advisors' perception that express the politcal administrative aspects of the reform and, in the second, the perception of the political view of what has changed concerning the management of the social politics